Peran Guru Kelas dan Orangtua pada Sekolah Ramah Anak untuk Mencegah dan Mengatasi Perundungan - Setiadi, Nanang; Purwanti, Purwanti; Widiatmoko, Anggoro; Agung Yuwono Putro , Ahmad (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2023)
Physical and verbal bullying is still rife in elementary schools. A Child-Friendly School (CFS) is a breakthrough that schools can take to prevent and overcome bullying. Teachers and parents have an important role in the success of CFS. The purpose of this study was to find out (1) the implementation of CFS, (2) the handling of bullying, and (3) teachers’ and parents’ role in preventing and handling bullying in schools. This research is qualitative research. This research was conducted at SD Negeri 3 Kadipiro in 2022. Data collection was carried out by interviews, observations, and documentation. The results of this study are (1) the implementation of CFS at SD Negeri 3 Kadipiro was carried out by declaring CFS, forming CFS team, creating a CFS program, designing complaints of violence mechanism, and involving parents through discussions about bullying in the Student-Parent Association (SPA) forum. (2) The handling of violence is implemented by designing fun learning activities such as play-based learning and watching interesting videos. (3) Guidance and counseling services are conducted to encourage students and parents to reflect on themselves. The goal is to realize on the causes and consequences of violence so that it can be solved and even prevented.